From Exclusion to Active Intergenerational Participation: A Dubbing Project in a Minoritised Indigenous Language - Montroy, Maria; García-Azkoaga, Inés María (Íkala, Revista de Lenguaje y Cultura, 2024)
Forro is a minority language in São Tomé and Príncipe (Africa) that coexists with Portuguese (the hegemonic language). It has limited social presence and minimal institutional support. It is predominantly spoken by the elderly, who experience significant social exclusion. This work is the result of a project with a twofold objective: firstly, to identify potential tools to enhance intergenerational relations and the social well-being of the elderly; secondly, to ascertain the impact of intergenerational language transmission activities on the broader community. The study is being conducted in collaboration with a non-governmental organisation for development in the Santo Amaro community. It is our contention that dubbing can be an instrument for intergenerational communication. In order to test this assertion, a workshop was designed in which a digital animation was dubbed with the participation of elderly individuals and children from the same community with the results of the activity undergoing a qualitative analysis. The benefits of a dubbing workshop, such as the one proposed, are confirmed in terms of its positive impact on different cultural and social aspects. It allows the rights of speakers to be made visible and promoted, as well as providing them with social projection, and breaking down interlinguistic barriers. On the one hand, the project has the potential to challenge existing intergenerational and cultural prejudices; on the other hand, the community benefits from a collaborative work that makes quality digital audiovisual material available to them, which was previously non-existent in this minoritised language.